Metformin in autosomal dominant polycystic kidney disease: experimental hypothesis or clinical fact? - Antonio Pisani; Eleonora Riccio; Dario Bruzzese; Massimo Sabbatini (BMC Nephrology, 2018)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) accounts for 8–10% of end-stage chronic kidney disease (CKD) patients worldwide. In the last decade, the advanced knowledge in genetics and molecular pathobiology of ADPKD focused some aberrant molecular pathways involved in the pathogenesis of the disease leading to controlled clinical trials aimed to delay its progression with the use of mTOR inhibitors, somatostatin or tolvaptan. Preclinical studies suggests an effective role of metformin in ADPKD treatment by activating AMPK sensor. Clinical trials are currently recruiting participants to test the metformin use in ADPKD patients. Methods We retrospectively examined the records of our ADPKD patients, selecting 7 diabetic ADPKD patients under metformin treatment and 7 matched non-diabetic ADPKD controls, to test the effect of metformin on renal progression during a 3 year follow-up. Results During the first year, the GFR decreased by 2.5% in Metformin Group and by 16% in Controls; thereafter, renal function remained stable in Metformin Group and further decreased in Controls, reaching a 50% difference after 3 years of observation. Accordingly, the overall crude loss of GFR, estimated by a linear mixed model, resulted slower in the Metformin than in Control Group (− 0.9; 95% C.I.: -2.7 to 0.9 vs - 5.0; 95% C.I.: -6.8 to − 3.2 mL/min/1.73 m2 per year, p = 0.002). Conclusions Our data are suggestive of a beneficial effect of metformin on progression of ADPKD. Large, randomized, prospective trials are needed to confirm this hypothesis.